Steroid induced ocular complications in idiopathic nephrotic syndrome: a cross sectional single center study - Zunaira Zulfiqar; Fatema Lanewala; Sabeeta Khatri; Irshad Bajeer; Madiha Aziz; Seema Hashmi (Journal of the Pakistan Medical Association)
Objective: To screen children receiving steroids to identify ocular complications and their prevalence.